2016
DOI: 10.3390/s16122163
|View full text |Cite|
|
Sign up to set email alerts
|

A Smartphone Application for Personal Assessments of Body Composition and Phenotyping

Abstract: Personal assessments of body phenotype can enhance success in weight management but are limited by the lack of availability of practical methods. We describe a novel smart phone application of digital photography (DP) and determine its validity to estimate fat mass (FM). This approach utilizes the percent (%) occupancy of an individual lateral whole-body digital image and regions indicative of adipose accumulation associated with increased risk of cardio-metabolic disease. We measured 117 healthy adults (63 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
(47 reference statements)
2
23
0
Order By: Relevance
“…24 Additionally, efforts have been made to predict body volume and body composition from 2D smartphone images. 25, 26 Fat mass predicted from height, weight, and measures obtained by a single 2D side view were not significantly different than fat mass measured by DXA. 25…”
Section: Validation Studiesmentioning
confidence: 66%
See 1 more Smart Citation
“…24 Additionally, efforts have been made to predict body volume and body composition from 2D smartphone images. 25, 26 Fat mass predicted from height, weight, and measures obtained by a single 2D side view were not significantly different than fat mass measured by DXA. 25…”
Section: Validation Studiesmentioning
confidence: 66%
“…25, 26 Fat mass predicted from height, weight, and measures obtained by a single 2D side view were not significantly different than fat mass measured by DXA. 25…”
Section: Validation Studiesmentioning
confidence: 66%
“…In addition, when the body volume estimates were combined with total body water measures from bioimpedance spectroscopy for a “field-based” three-compartment model, there were very large correlations (r = 0.96 to 0.99) with the laboratory method for FM and FFM [ 10 ]. Moreover, Farina et al [ 26 ] showed no significant differences, strong relationships (R 2 = 0.91 to 0.95), and a small standard error of estimate values (±2.71 to 2.83 kg) when comparing FM estimates from a different 2D body composition program to dual-energy X-ray absorptiometry. It should be noted that the 2D image system of Farina et al [ 26 ] predicts body volume from the number of pixels comprised by a person’s body within an image.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Farina et al [ 26 ] showed no significant differences, strong relationships (R 2 = 0.91 to 0.95), and a small standard error of estimate values (±2.71 to 2.83 kg) when comparing FM estimates from a different 2D body composition program to dual-energy X-ray absorptiometry. It should be noted that the 2D image system of Farina et al [ 26 ] predicts body volume from the number of pixels comprised by a person’s body within an image. This is a different process than the 2D technique of the current study and Fedewa et al [ 10 ], which estimates body composition by the width of various anatomical dimensions within the image.…”
Section: Discussionmentioning
confidence: 99%
“…The Hamamatsu technology and other similar high‐resolution scanning technologies have limited availability because of cost. Consequently, there has been a recent surge in the development of laser‐based imaging technologies and associated applications driven largely by the demand for devices that estimate body composition and body shape easily and for personalized health assessments in weight management. The devices currently being marketed have lower resolution and sensitivity compared with the 3DPS scanner reported here.…”
Section: Discussionmentioning
confidence: 99%